TRAUMATIC INJURIES OF THE PRIMARY DENTITION PRESENTED IN AN UNIVERSITARY EMERGENCY SERVICE - Mihaela Tanase; Daciana Zmarandache; Aneta Munteanu; Ioana Stanciu (Romanian Dental Association for Education, 2019)
Objective. To asses the frequency and distribution of traumatic dental injuries (TDI) in primary teeth (PT) in patients treated at a pediatric dental emergency service. Material and method. Retrospective study on 425 patients (229 boys) aged 1-6 years, referred to Pedododntics Department, Carol Davila University Bucharest, over a year. The prevalence and distribution of TDI according to age, sex, number of affected teeth, topography and type of trauma, time to presentation were evaluated. Results. Prevalence of TDI was 8.1%, boys (60%) being SS more affected (p <0.05). Children under the age of 3 were the most affected (40.5%) followed by children aged 4 (24.5%). 54% of patients had periodontal injuries (54%), most patients having affected at least 2 PT. Maxillary front teeth were most affected (SS, p <0.05). Almost 1/3 were luxations, followed by subluxations (¼). 40% of patients presented during 12 hours after the trauma. Conclusions. TDI in PT represent a pediatric emergency, therefore the persons concerned (parents, educators, pediatricians) must be correctly informed about the necessity of early treatment.